Sustainable Development of the Mortgage Market in Azerbaijan: Commercial Risks of Housing Construction, Social Vision, and State Influence - Ganbarov, Fuad; Smoląg, Klaudia; Muradov, Rashad; Aghayeva, Konul; Jafarova, Rumella; Mammadov, Yashar (MDPI AG, 2020)
The purpose of this study is to formulate a model for sustainable development of the mortgage market in Azerbaijan, taking into account commercial risks of housing construction, the risks of the construction industry, social visions of mortgages, state pressure, and support. The following five key research stages can be distinguished. Namely, identification of commercial risks of housing construction based on a survey; evaluation of the effectiveness of risk diversification strategy; determination of the social vision of a mortgage; substantiating the main directions of state pressure and support for mortgage market development; and creation of a model for sustainable development of the mortgage market in Azerbaijan. At the same time, it is proposed to use a methodological approach to assessing the effectiveness of the model based on the construction of the multivariate linear regression equation. The inclusive model of sustainable development of the mortgage market in Azerbaijan provides for the formation of a favorable institutional environment. Given the selected modules, forecasting the effectiveness of the proposed inclusive model demonstrates its effectiveness in the direction of enhancing mortgage lending based on interest rate regulation taking into account the benefits of green housing construction.